Characteristics of small pancreatic neuroendocrine tumors and risk factors for invasion and metastasis - Mei, Wentong; Cao, Feng; Lu, Jiongdi; Qu, Chang; Fang, Zhen; Li, Jia; Li, Fei (Frontiers in Endocrinology, 2023)
Background: The number of people with small pancreatic neuroendocrine tumors (pNETs) (tumors with a diameter less than or equal to 2 cm) is gradually increasing, but the selection of treatment strategy is still controversial. Our aim was to characterize small pNETs with a poor prognosis and to define the impact of aggressive small pNETs on survival and the risk factors for the development of invasive disease. Methods: Patients with pNETs diagnosed between 2004 and 2019 and a tumor diameter of 2 cm or less were selected from the SEER Registry. Kaplan‒Meier survival analysis was used to identify the factors affecting patient survival, and binary logistic regression was used to identify the associated risk factors. Results: A total of 3261 patients with pNETs were enrolled in the study. Both older and younger patients benefited from surgery. Regional invasion occurred in 10% of the patients, and distant metastases occurred in 9% of the patients, but in both categories, those who underwent surgery had better survival outcomes than those who did not. There was no difference in survival between patients with a tumor diameter of 1–2 cm and those with a tumor diameter of less than 1 cm, and there was no difference in survival between patients with functional and nonfunctional small pNETs. However, the survival of patients with pNETs in the head of the pancreas was worse than that of patients with tumors in other parts of the pancreas. Survival was worse in elderly patients and in those with poorly differentiated and undifferentiated tumors. Lymphatic metastasis, regional invasion, and distant metastasis all worsened the prognosis of patients. The presence or absence of neuroendocrine function, the degree of tumor differentiation, and the location of the tumor were associated with the risk of lymphatic metastasis and regional invasion; the risk factors for distant metastasis were associated with the degree of differentiation and tumor location. Conclusions: The pNETs ≤ 2 cm in diameter could be still aggressive, and patient prognosis worsens after invasive disease develops. Attention to the characteristics of aggressive tumors can improve patient survival.